Potential production simulation and optimal nutrient management of two hybrid rice varieties in Jinhua, Zhejiang Province, China - Xie, Wen-xia (Zhejiang University Press, 2007)

(untitled)
Potential growth of two widely-grown hybrid rice varieties in the Jinhua district of Zhejiang Province, Shanyou63 for mid-rice and Xieyou46 for late rice, was simulated using a crop growth model of WOFOST. Parameters of the rice growth in WOFOST were calibrated through field experiments from 1999 to 2002 in Jinhua. The potential yield simulated with WOFOST was about 12 t/ha for Shanyou63 and 10 t/ha for Xieyou46, which are in good agreement with the highest recorded yield obtained in this area. Under farmers practice, current yield is about 7.5 t/ha for Shanyou63 and 6.5 t/ha for Xieyou46. There is a gap between the actual rice yield and the potential yield for these two hybrid rice varieties grown in this area. The attainable target yields were set to 70% to 75% of their potential yields for the two varieties. A recently developed software “Nutrient Decision Support System (NuDSS)” for irrigated rice was used to optimize nutrient management for these two rice varieties. According to NuDSS, the optimal fertilizer N requirement for the target yields was about 150 kg/ha for Shanyou63 and about 120 kg/ha for Xieyou46, which were only about 70% of the fertilizer N application under current farmers’ practice. Comparing with farmers’ practice, there is great potential to increase actual rice yields and to reduce fertilizer N use rates by improving rice crop management practice in Jinhua.